Fibroids 2021
DOI: 10.5772/intechopen.94162
|View full text |Cite
|
Sign up to set email alerts
|

Physiopathology and Management of Uterine Fibroids

Abstract: Uterine fibroid is the most encountered benign tumour in women of reproductive age. It causes spontaneous abortions, missed abortions, painful red degeneration or infarction of the fibroids, abnormal foetal presentation, obstructed labour, and an increased likelihood of premature deliveries, caesarean deliveries, postpartum haemorrhage in pregnancy, whereas, in the non-pregnant women it is associated an irregular menstrual cycle sometimes associated with heavy menstrual bleeding, infertility, constipation, uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(27 reference statements)
1
1
0
1
Order By: Relevance
“…Haji Adam Malik General Hospital is a class A general hospital and serves as a referral center for the North Sumatra region and its surroundings, along with the development of the medical profession because there are more and more obstetrics and gynecology specialists in the area who play a role in early diagnosis of cases of both AUB and malignancy, so that referrals are made to more competent health facilities when screening patients in regional hospitals. 13 17 in Cameroon showed similar results and found that the majority of leiomyoma locations were submucosal (89.4%).…”
Section: Resultssupporting
confidence: 58%
“…Haji Adam Malik General Hospital is a class A general hospital and serves as a referral center for the North Sumatra region and its surroundings, along with the development of the medical profession because there are more and more obstetrics and gynecology specialists in the area who play a role in early diagnosis of cases of both AUB and malignancy, so that referrals are made to more competent health facilities when screening patients in regional hospitals. 13 17 in Cameroon showed similar results and found that the majority of leiomyoma locations were submucosal (89.4%).…”
Section: Resultssupporting
confidence: 58%
“…Л ейоміому матки (ЛМ) на сьогодні розглядають як доброякісну істинну пухлину матки, що не просто розвивається в міометрії, а виникає з гладком'язової тканини міометрію незалежно від наявності або відсутності фібропластичного компонента у вузлах пухлини і рівня гормонозалежності. ЛМ є моноклональною пухлиною, тобто зростання її походить з од-нієї первинної мутантної клітини, яка набуває здатності нерегульованого поділу [24]. Поширеність ЛМ під час вагітності коливається в межах від 10,7% до 16,7% [4,16].…”
Section: вступunclassified
“…Cytogenetic studies have shown that approximately 40%–50% of UF harbor chromosomal abnormalities and linked to changes in a number of genes, including MED12, HMGA2, COL4A5/COL4A6, and FH genes ( McGuire et al, 2012 ; Segars et al, 2014 ). Studies have demonstrated that from total genetic aberration, about 70%–80% of uterine leiomyoma’s shown site-specific somatic mutation on mediator complex subunit 12 ( MED12 ) genes in different populations, including Finnish (Caucasian), northern United States regions, and South African women ( Mittal et al, 2015 ; Noutakdie Tochie et al, 2021 ). These studies suggest the need to have ethnic or population specific genetic data to gain insight into the disease etiology.…”
Section: Introductionmentioning
confidence: 99%